2018
DOI: 10.4081/pmc.2018.193
|View full text |Cite
|
Sign up to set email alerts
|

Kearns-Sayre syndrome is genetically and phenotypically heterogeneous

Abstract: We do not agree with the statement that cerebral white matter lesions (WMLs) found on imaging are unique to KSS patients. 1 Patchy or diffuse subcortical WMLs are a frequent finding in mitochondrial disorders (MIDs) with cerebral involvement. Particularly, patients with non-specific mitochondrial syndromes show up with WMLs as described in Berio's case. 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…According to mitochondrial myopathies [38][39][40], fortunately episodes of RM are infrequent and only a few examples will be analysed below. Generally, mitochondrial myopathy can be classified into 5 groups: 1) mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) [38], 2) myoclonus epilepsy associated with ragged-red fibres (MERRF) [41,42], 3) Kearns-Sayre syndrome (KISS) [43], 4) chronic progressive external ophthalmoplegia (CPEO) [44], and 5) neurogenic weakness with ataxia and retinitis pigmentosa (NARP) [45,46].…”
Section: Mitochondrial Myopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to mitochondrial myopathies [38][39][40], fortunately episodes of RM are infrequent and only a few examples will be analysed below. Generally, mitochondrial myopathy can be classified into 5 groups: 1) mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) [38], 2) myoclonus epilepsy associated with ragged-red fibres (MERRF) [41,42], 3) Kearns-Sayre syndrome (KISS) [43], 4) chronic progressive external ophthalmoplegia (CPEO) [44], and 5) neurogenic weakness with ataxia and retinitis pigmentosa (NARP) [45,46].…”
Section: Mitochondrial Myopathiesmentioning
confidence: 99%
“…The KISS syndrome has a typical onset before the age of 20 and manifests with progressive external ophthalmoplegia, pigmentary retinopathy, and cardiac conduction block, hyperproteinorrhachia or ataxia [43].…”
Section: Kiss Syndromementioning
confidence: 99%
“…ure, or cardiac disease [4]. Concerning cardiac involvement, the most frequently reported condition is third-degree atrioventricular block, which requires implantation of a pacemaker.…”
mentioning
confidence: 99%
“…It is only reported that the index patient was of short stature, had retinitis pigmentosa, hypoacusis, and myopathy [ 1 ]. However, KSS patients may also present with endocrine abnormalities (e.g., diabetes or hypogonadism), renal failure, or cardiac disease [ 4 ]. Concerning cardiac involvement, the most frequently reported condition is third-degree atrioventricular block, which requires implantation of a pacemaker.…”
mentioning
confidence: 99%
“…We do not agree with the definition of KSS. Diagnostic criteria for KSS not only include ophthalmoplegia, onset <20 y, retinopathy, and cardiac conduction defects,1 but also short stature, elevated CSF protein, and endocrine abnormalities 4…”
mentioning
confidence: 99%